The economywide impacts of climate change on Philippine agriculture - Rosegrant, Mark W.; Perez, Nicostrato D.; Pradesha, Angga; Thomas, Timothy S. (International Food Policy Research Institute, 2015)
It has been widely shown for most countries that high productivity growth in the agricultural sector is a key driver of structural transformation to promote long-term economic growth. Historically, low agricultural productivity growth has hindered economic growth and employment creation in the Philippines, where agricul-ture—which accounts for one-third of employment—re-mains a key sector. Climate change has the potential to disrupt crop productivity, and in turn affect domestic agricultural production, consumption, and food secu-rity. Moreover, the global impact of climate change could stimulate changes in international and national commodity prices that ultimately have negative effects on both Philippine agriculture and the country’s overall economy.